EXTH-09. DIANHYDROGALACTITOL (VAL-083) HAS THE POTENTIAL TO OVERCOME MAJOR CHALLENGES IN THE TREATMENT OF DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (5th November 2018) - Steino, Anne; Zhai, BeiBei; Yang, Xiaodong; Kline, Cassie; Bacha, Jeffrey; Brown, Dennis; Daugaard, Mads; Mueller, Sabine
Abstract: OBJECTIVE: VAL-083 is a structurally unique bi-functional DNA targeting agent that readily crosses the blood-brain barrier and accumulates in brain tumor tissue. Herein we assess the activity of VAL-083 as single agent as well as in combination regimens including Wee1 Kinase inhibitor AZD1775 and radiation therapy in patient derived model systems of DIPG. METHODS: DIPG derived cell lines SF8628 and NEM157 (H3.3K27) as well as SF10693 (H3.1K27M) and pediatric glioblastoma cell lines SF188 (H3.3K27 wildtype) were treated with increasing concentrations of single agent VAL-083 as well as in combination with AZD1775 and radiation therapy. To determine potential synergistic activity, we applied the Chou-Talalay method, which allows the quantitative determination of drug interactions by calculating a combination index (CI). In vivo activity of VAL-083 as single agent as well as in combination with AZD1775 was assessed in an orthotopic engraftment model of pediatric DIPG (SF8628). RESULTS: The IC50 of VAL-083 ranged from 2.1uM to 19.7uM. The combination of VAL-083 and AZD1775 showed synergistic activity in all tested cell lines with CI ranging from 0.405 to 2.066 with < 1 indicating synergy whereas VAL-083 combined with radiation therapy led to only additive effects. Initial in vivo study showed that combined treatment with VAL-083 and AZD1775 conferred greater survival benefit to mice with engrafted DIPG tumors compared to control as well as single agent treatment. Day 49 after therapy initiation shows: Control: 2/10; AZD1775: 4/10; VAL083 7/10 and VAL-083+AZD1775: 11/11 mice alive. CONCLUSION: Our present study highlights that the combination of VAL-083 and AZD1775 might be a promising new therapeutic strategy for children with DIPG. Ongoing studies will continue to assess the in vivo activity as well explore the underlying mechanism of action of the combination strategy.